Overconfident How Economic and Health Fault Lines Left the Middle East and North Africa Ill-Prepared to Face COVID - Gatti, Roberta (The World Bank, 2021)
Overconfident: How Economic and Health Fault Lines Left the Middle East and North Africa Ill-Prepared to Face COVID This report examines the region's economic prospects in 2021, forecasting that the recovery will be both tenuous and uneven as per capita GDP level stays below pre-pandemic levels. COVID-19 was a stress-test for the region's public health systems, which were already overwhelmed even before the pandemic. Indeed, a decade of lackluster economic reforms left a legacy of large public sectors and high public debt that effectively crowded out investments in social services such as public health. This edition points out that the region's health systems were not only ill-prepared for the pandemic, but suffered from over-confidence, as authorities painted an overly optimistic picture in self-assessments of health system preparedness. Going forward, governments must improve data transparency for public health and undertake reforms to remedy historical underinvestment in public health systems
Keywords: Current Account; Economic Growth; External Balances; Fiscal Balance; Oil; Oil and Gas; Oil Exporters; Oil Importers; Oil Prices; Productivity